Temperature-induced self-sealing capability of Banksia follicles. Issue 143 (20th June 2018) - Huss, Jessica C.; Spaeker, Oliver; Gierlinger, Notburga; Merritt, David J.; Miller, Ben P.; Neinhuis, Christoph; Fratzl, Peter; Eder, Michaela
Abstract : Many plants in fire-prone regions retain their seeds in woody fruits in the plant canopy until the passage of a fire causes the fruit to open and release the seeds. To enable this function, suitable tissues are required that effectively store and protect seeds until they are released. Here, we show that three different species of the Australian genus Banksia incorporate waxes at the interface of the two valves of the follicle enclosing the seeds, which melt between 45°C and 55°C. Since the melting temperature of the waxes is lower than the opening temperatures of the follicles in all investigated species ( B. candolleana, B. serrata, B. attenuata ), we propose that melting of these waxes allows the sealing of micro-fissures at the interface of the two valves while they are still closed. Such a self-sealing mechanism likely contributes to the structural integrity of the seed pods, and benefits seed viability and persistence during storage on the plants. Furthermore, we show in a simplified, bioinspired model system that temperature treatments seal artificially applied surface cuts and restore the barrier properties.